Niche separation of comammox Nitrospira and canonical ammonia oxidizers in an acidic subtropical forest soil under long-term nitrogen deposition. (November 2018) - Shi, Xiuzhen; Hu, Hang-Wei; Wang, Jianqing; He, Ji-Zheng; Zheng, Chengyang; Wan, Xiaohua; Huang, Zhiqun
Abstract: The recent discovery of comammox Nitrospira capable of converting ammonia to nitrate in a single organism radically challenged our century-long perception of the classic two-step nitrification performed by ammonia oxidizers and nitrite oxidizers. However, our understanding of the niche separation of comammox Nitrospira and canonical nitrifiers in forest ecosystems remains limited, especially under a global scenario of elevated nitrogen (N) deposition. Here we evaluated the impacts of six-year N deposition on the dynamics of comammox Nitrospira, ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) in a subtropical forest soil. Soil inorganic N concentrations significantly increased under the six-year simulation of N deposition, while soil pH, available phosphorus, total carbon (C), C/N ratio and microbial biomass significantly decreased. Quantitative PCR showed that the amoA gene abundances of comammox Nitrospira clade B and AOA substantially increased under the increasing rates of N deposition. By contrast, the AOB amoA gene abundance significantly decreased with the higher levels of N deposition (100 and 150 kg N ha −1 yr −1 ). Increased 13 CO2 incorporation into the AOA communities, rather than comammox Nitrospira or AOB, was demonstrated in a DNA-stable isotope probing microcosm, indicative of the capacity of AOA to assimilate 13 CO2 through autotrophic nitrification in the investigated subtropical forest soil under long-term N deposition. Phylogenetic analysis revealed that the autotrophic AOA assemblages belonged to the Nitrosotalea cluster, and their capacity for assimilating CO2 through autotrophic nitrification was not affected by the long-term N deposition. Taken together, we provided new evidence for the niche separation of comammox Nitrospira and canonical ammonia oxidizers in soil nitrification under the long-term N deposition in the acidic subtropical forest soil. Highlights: The abundances of comammox Nitrospira clade B and AOA increased with N input. The abundance of AOB decreased with N input rates higher than 100 kg N ha −1 yr −1 . Increased 13 CO2 was only incorporated into soil AOA through autotrophic pathway. N input showed no effect on autotrophic AOA within the Nitrosotalea cluster.